Hephaistos : god of fire - O'Connor, George (O'Connor, George. Olympians, 2019)
Shares the story of the legend of Hephaistos and the wrath he brought upon those who belittled and hurt him. Presented as a graphic novel. Includes detailed notes and text-related discussion questions.